Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Penghindaran Pajak (Tax Avoidance) - Rachmat Sulaeman (Ridwan Institute, 2021)
This study aims to analyze the effect of profitability, leverage and company size on tax avoidance. The dependent variable in the study was tax avoidance as measured by using the cash effective tax rate (CETR). This study selects the object of research in the form of financial reports from property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. The number of research samples of 30 companies obtained by purposive sampling method with data analysis techniques using multiple linear regression analysis. The results of the analysis show that profitability and company size have a significant positive effect on tax avoidance. This shows that the higher the profitability and company size, the higher the tax avoidance, but in this study Leverage has a significant negative effect on tax avoidance. This shows that the higher the leverage, the lower the tax avoidance.